The Influence Of Company Value On Share Price In Automotive Companies Listed On The Indonesian Stock Exchange - ayu andini; Muchriana Muchran; Nasrullah, Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to determineThe Influence of Company Value on Share Prices in Automotive Companies Listed on the Indonesian Stock Exchange. In this research, the method used is a quantitative method with classic assumption tests involving normality tests, auto correlation tests and heteroscedasticity tests. This research uses simple regression analysis with hypothesis testing consisting of a partial significant test (t statistical test) and the coefficient of determination (R-Square). The population in this study consisted of 12 companies on the Indonesian Stock Exchange. The research sample selected based on criteria was 12 companies on the Indonesia Stock Exchange for 2020-2022 so that the data used was 36 companies' financial reports. The technique used to collect data in this research is the documentation method using secondary data sources (financial reports) according to the research period. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 29 application regarding the influence of company value on share prices in automotive companies listed on the Indonesian Stock Exchange which was discussed in the previous chapter, the author draws the conclusion thatCompany value has a positive and significant influence on share prices in the automotive sector listed on the Indonesia Stock Exchange.